Anti-bacterial activity of Annona muricata Linnaeus extracts: a systematic review - Silva, Ricardo Mendes da (2022)
Current analysis systematically reviews data available in the literature on the anti-bacterial activity of Annona muricata extracts (AME) against Staphylococcus aureus and Escherichia coli. Search was undertaken at four electronic databases and studies’ quality were assessed. Results were summarized and Minimum Inhibitory Concentration (MIC) of AME (versus antimicrobial control) against S. aureus and E. coli was the main datum analyzed. The initial database search yielded 2,433 results. We selected 14 studies and four were used for meta-analysis. The MIC ranged between 156 μg/mL and 1,024 μg/mL against S. aureus and between 256 μg/mL and 1,024 μg/mL against E. coli. The different strains of E. coli studied were more sensitive to AME than those of S. aureus. The differences mean concentrations and standard deviations between AME and antimicrobials were 101.91 and 946.05 for E. coli, and 388.90 and 970.61 for S. aureus respectively. The heterogeneity of data is highlighted. Different methodologies were used, several studies didn’t include antibiotics as control, antibiotics were different and various concentrations of extracts were tested. Studies showed possibilities of the plant under analysis as a source of new phytochemical compounds against microorganisms.